1989
DOI: 10.1111/j.1745-9125.1989.tb00867.x
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Arrest for Wife Assault*

Abstract: The social meaning of wife assault has changed in recent years for both citizens and formal social control agents. Research on deterrence has been partly responsible for modiyying police responses to domestic violence. Police are increasingly adopting pro-arrest policies for wife assault, but little is known about perceptions held by assaulters concerning the consequences of arrest for their life circumstances. Using national survey data from samples of both assaultive and nonassaultive men, the following ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…As a result, most rational choice studies of rule violation have used single-sex samples (Williams and Hawkins 1989;Bachman et al 1992) or have only included gender in estimated models as a control variable (Michaels and Miethe 1989;Paternoster and Simpson forthcoming). However, recent studies of deviant behaviors (Finley and Grasmick 1985;Miller and Simpson 1991;Grasmick, Blackwell, and Bursik 1993b) have found significant gender differences in both levels and effects of key explanatory variables, especially variations regarding perceptions of situational circumstances (Liu and Kaplan 1996;Tibbetts and Herz 1996), such as formal and informal punishments.…”
Section: Gender Differences In Students' Rational Decisions To Cheatmentioning
confidence: 95%
See 1 more Smart Citation
“…As a result, most rational choice studies of rule violation have used single-sex samples (Williams and Hawkins 1989;Bachman et al 1992) or have only included gender in estimated models as a control variable (Michaels and Miethe 1989;Paternoster and Simpson forthcoming). However, recent studies of deviant behaviors (Finley and Grasmick 1985;Miller and Simpson 1991;Grasmick, Blackwell, and Bursik 1993b) have found significant gender differences in both levels and effects of key explanatory variables, especially variations regarding perceptions of situational circumstances (Liu and Kaplan 1996;Tibbetts and Herz 1996), such as formal and informal punishments.…”
Section: Gender Differences In Students' Rational Decisions To Cheatmentioning
confidence: 95%
“…7 Still, rational choice models of deviance have been used to explain a broad range of rule breaking: (a) income-tax evasion (Klepper and Nagin 1989), (b) sexual assault (Bachman, Paternoster, and Ward. 1992), (c) domestic violence (Williams and Hawkins 1989), (d) larceny-theft (Nagin and Paternoster 1993;Tib-1 Many of the basic assumptions and propositions of rational choice theory, such as those concerning individual perceptions of formal punishments, can be traced to classical deterrence theory (Zimring and Hawkins 1973;Gibbs 1975). In addition, key constructs and theoretical predictions of rational choice theory are quite similar to those of economic models of behavior (Becker 1968;Bunn, Caudill and Grapper 1992), reasoned action-planned behavior theories (Beck and Ajzen 1991;Genereux and McLeod 1995), or social learning perspectives of offending (Akers 1985).…”
Section: Gender Differences In Students' Rational Decisions To Cheatmentioning
confidence: 99%
“…Sherman and Berk (1984), in a field experiment on domestic violence, found that arrested subjects showed significantly less subsequent violence than those not arrested. Furthermore, Green (1989) and Grasmick and Bursik (1990) showed that the possibility of informal sanctions resulting from formal sanctions, not the formal sanctions themselves, was responsible for people being deterred from rule violations (see also Williams and Hawkins 1989).…”
Section: Consequences Of Negative Social Sanctionsmentioning
confidence: 96%
“…That is, an individual may refrain from criminal behavior out of fear of what his (or her) parents, significant others, friends, and employers will do once they learn of his (or her) arrest (Williams and Hawkins 1989;Zimring and Hawkins 1973). However, most researchers have considered legal and extralegal deterrents additively and found that informal sanctions exert a strong and independent influence on criminal involvement (see, e.g., Grasmick and Bursik 1990).…”
Section: Beyond Legal Sanctionsmentioning
confidence: 97%
“…Such studies distinguish two extralegal forms of punishment: (1) self-imposed sanctions such as guilt, resulting from behavior that an actor knows is morally wrong, and (2) socially imposed sanctions such as social disapproval, which occur when an actor's significant others (e.g., family, friends, employers, professors) become aware of the actor's criminal behavior (Grasmick and Bursik 1990;Makkai and Braithwaite 1994). For example, Grasmick and Kobayashi (2002) differentiate between selfimposed shame and socially imposed embarrassment, Williams and Hawkins (1989) between self-stigma and social stigma, control theorists between internal (e.g., conscience) and external (e.g., parental reaction) controls (Gottfredson and Hirschi 1990;Hirschi 1969;Nye 1958;Reiss 1951), and developmental psychologists between guilt-induction and social shaming (see Braithwaite 1989:54). Although Braithwaite (1989:57) makes a distinction between the loss of social approval and conscience as potential deterrents, he argues that to shame and to induce guilt are inextricably part of the same cultural process of shaming.…”
Section: Beyond Legal Sanctionsmentioning
confidence: 99%